The expression of irx7 in the inner nuclear layer of zebrafish retina is essential for a proper retinal development and lamination. - Yuqing Zhang; Yifan Yang; Caleb Trujillo; Wenxuan Zhong; Yuk Fai Leung (PLoS ONE)
Irx7, a member in the zebrafish iroquois transcription factor (TF) family, has been shown to control brain patterning. During retinal development, irx7's expression was found to appear exclusively in the inner nuclear layer (INL) as soon as the prospective INL cells withdraw from the cell cycle and during retinal lamination. In Irx7-deficient retinas, the formation of a proper retinal lamination was disrupted and the differentiation of INL cell types, including amacrine, horizontal, bipolar and Muller cells, was compromised. Despite irx7's exclusive expression in the INL, photoreceptors differentiation was also compromised in Irx7-deficient retinas. Compared with other retinal cell types, ganglion cells differentiated relatively well in these retinas, except for their dendritic projections into the inner plexiform layer (IPL). In fact, the neuronal projections of amacrine and bipolar cells into the IPL were also diminished. These indicate that the retinal lamination issue in the Irx7-deficient retinas is likely caused by the attenuation of the neurite outgrowth. Since the expression of known TFs that can specify specific retinal cell type was also altered in Irx7-deficient retinas, thus the irx7 gene network is possibly a novel regulatory circuit for retinal development and lamination.